An aqueous polyisocyanate adhesive with excellent bond durability for engineered wood composites enhanced by polyamidoamine-epichlorohydrin co-crosslinking and montmorillonite hybridization. (January 2022) - Fan, Bo; Kan, Haofeng; Kan, Yufei; Bai, Yumei; Han, Guangping; Bai, Long; Zhang, Shifeng; Gao, Zhenhua
Abstract: Recent trends toward mass-timber buildings and tall timber structures necessitate more stringent requirements for the bond durability of adhesives for engineered wood composites. In this work, a cost-effective strategy for manufacturing a novel aqueous polyisocyanate adhesive with excellent hygrothermal resistance for engineered wood composites was produced via co-crosslinking with polyamidoamine-epichlorohydrin (PAE) resin followed by organic–inorganic hybridization with montmorillonite clay (MMC). Test results confirmed that PAE co-crosslinking effectively increased the crosslinking density of aqueous polyisocyanate adhesive meanwhile prolonged working life. Hybridization of PAE-crosslinked polyisocyanate with MMC resulted in compact crosslinked networks and notably increased hygrothermal resistance. Consequently, this novel aqueous polyisocyanate adhesive exhibited excellent bond durability of plywood in terms of a wet aged strength of 1.73 MPa and a strength reduction ratio of only 18.4% after 7 boiling-dry hygrothermal aging cycles, which satisfies the requirements for manufacturing engineered wood composites as good construction and building materials.